Clinical Characteristics of Enthesitis-Related Arthritis and Outcomes of Treatment with Salazosulfapyridine - Yuko Akutsu; Yuko Hayashi; Masaaki Mori; Masaki Shimizu (Modern Rheumatology, 2026)
Abstract Objectives Enthesitis-related arthritis (ERA), characterized by chronic arthritis and/or enthesitis, is a relatively rare subtype of juvenile idiopathic arthritis (JIA). Achieving sustained disease control can be challenging. We aimed to characterize ERA and to evaluate the efficacy of salazosulfapyridine (SASP) treatment. Methods We retrospectively reviewed 23 patients with ERA treated in our institute between 2015 and 2025. Clinical characteristics, laboratory findings, and treatment courses were analyzed descriptively. Patients were categorized into three groups based on treatment escalation following NSAID therapy. Results The median age at onset was 10 years, and median disease duration before diagnosis was 11 months; 47.8% were females. Axial involvement was present in 65.2%, and psychological comorbidities in 52.2%. Nineteen patients received SASP; four who were younger at onset and had lower CRP levels at diagnosis were maintained on SASP monotherapy without treatment escalation. Active joint and enthesitis counts generally improved during follow-up, although some patients had persistent disease activity at 12 months. No severe adverse events were observed. Conclusions Diagnostic delay and psychological comorbidities were characteristic of ERA. SASP may be beneficial in selected patients with lower inflammatory activity at diagnosis; prospective studies are needed to better define its role in ERA management.